On species related to Elachista deceptricula Staudinger, 1880 with descriptions of three new species (Lepidoptera: Elachistidae) - L. Kaila; K. Nupponen (SHILAP)
The taxonomy of Palearctic Elachista species similar to E. deceptricula Staudinger, 1880 is revised. Five species are treated: E. spumella Caradja, 1920, E. deceptricula Staudinger, Elachista athroa Kaila, sp. n. from Turkey, E. conferta Kaila sp. n. from Spain, and E. sagara Kaila sp. n. from Kyrgyzstan. Lectotype is designated for E. spumella Caradja. These species are assigned to the Elachista dispilella complex sensu Kaila in Elachista subgenera Aphelosetia. The E. dispilella complex now comprises 24 species.